Control of grid connected inverter system for sinus oidal current injection with improved performance - Simeen. S. Mujawar.; Prof. Mrs. G. M. Karve (International Journal of Innovations in Engineering Research and Technology, 2021)
The control strategy for the grid connected inverter (GCI) during abnormal conditions like voltage sag, swell and line to ground fault has been presented. The strategy adopted here operates even during faulty conditions, unlike the conventional controller which fails to operate during fault y conditions. The Multi-Reference Frame (MRF) PI Controller is used for this purpose. In order to study the D ynamic Performance of the system, it is simulated in Matlab Simulink environment. The overall system is simulated for normal condition that is without the presence of fault, and with the presence of fault. The performance is also studied during abnormal conditions of the grid and its results are analyzed. The simulat ion results exhibit improved performance of the system during normal as well as abnormal conditions.